University-related factors in technology integration: a quantitative study in East Coast of China / Lin Chenhui, Geethanjali Narayanan and Harrinni Md Noor - Chenhui, Lin; Narayanan, Geethanjali; Md Noor, Harrinni (Universiti Teknologi MARA, 2024)
The Chinese government has acknowledged the importance of technology in education and has launched many policies to promote technology integration. Nevertheless, practical implementation still needs to match the expectations. Previous studies indicate that the integration of technology by English as a Foreign Language (EFL) lecturers is influenced by both initiate-order factors (e.g., facilitating conditions, university culture, policies and professional development) and subsequent-order factors (e.g., teacher beliefs, technological knowledge and skills). In China, initiate-order factors play a more significant role due to its collectivist culture. Thus, the objective of this study is to explore how university-related factors (representatives of initiate-order factors), including university culture, facilitating conditions, and professional development, affect EFL teachers’ technology integration and the interrelationship among these aspects. Technology integration in this study refers to the utilization of technology to facilitate transformative learning and teaching, rather than merely technology usage. A survey was adopted to examine university-related aspects of 271 EFL lecturers in East Coast of China. The data was analyzed using Partial Least Square–Structural Equation Modelling (PLS-SEM) in Smartpls 4. The findings revealed that facilitating conditions had a positive correlation with technology integration, whereas university culture and professional development showed weak relationships. University culture indirectly predicted technology integration via facilitating conditions. It also revealed that there was a positive correlation between university culture and professional development.